NOVELTIES IN BRAZILIAN BEGONIACEAE IV: Taxonomic notes - Kollmann, Ludovic Jean Charles (Phytotaxa, 2020)
As a result of a taxonomic study on Begoniaceae from Brazil, nine new synonyms are proposed and two species are restored from synonymy. Eleven names are lectotypified and two are neotypified.